Phacomatosis pigmentokeratotica is caused by a postzygotic HRAS mutation in a multipotent progenitor cell - Größer, Leopold; Herschberger, Eva; Sagrera, Ana; Shwayder, Tor; Flux, Katharina; Ehmann, Laura; Wollenberg, Andreas; Torrelo, Antonio; Bagazgoitia, Lorea; Diaz-Ley, Blanca; Tinschert, Sigrid; Oschlies, Ilske; et al. (The journal of investigative dermatology, 2013)
Phacomatosis pigmentokeratotica (PPK) is a rare epidermal nevus syndrome characterized by the co-occurrence of a sebaceous nevus and a speckled lentiginous nevus. The coexistence of an epidermal and a melanocytic nevus has been explained by two homozygous recessive mutations, according to the twin spot hypothesis, of which PPK has become a putative paradigm in humans. However, the underlying gene mutations remained unknown. Multiple tissues of six patients with PPK were analyzed for the presence of RAS, FGFR3, PIK3CA, and BRAF mutations using SNaPshot assays and Sanger sequencing. We identified a heterozygous HRAS c.37G>C (p.Gly13Arg) mutation in four patients and a heterozygous HRAS c.182A>G (p.Gln61Arg) mutation in two patients. In each case, the mutations were present in both the sebaceous and the melanocytic nevus. In the latter lesion, melanocytes were identified to carry the HRAS mutation. Analysis of various nonlesional tissues showed a wild-type sequence of HRAS, consistent with mosaicism. Our data provide no genetic evidence for the previously proposed twin spot hypothesis. In contrast, PPK is best explained by a postzygotic-activating HRAS mutation in a multipotent progenitor cell that gives rise to both a sebaceous and a melanocytic nevus. Therefore, PPK is a mosaic RASopathy.